Pola Interaksi Ternak dan Tanaman Pada Simantri 116 Desa Katung, Kecamatan Kintamani, Kabupaten Bangli - I W. Sunada; Dwi Putra Darmawan; I G. Setiawan Adi Putra (JURNAL MANAJEMEN AGRIBISNIS, 2014)
The program is integrated farming systems by farmers. One of the groups that implement integrated farming system with cattle horticultural crops is gapoktan Budi Luhur. The study aims to determine the income  farmers in the farm in the village of  Simantri 116 uncertain , the district of Kintamani , Bangli Regency , based on patterns of integration between horticultural crops, cattle, land management and crop rotation on the farm in the village of  Simantri 116 uncertain, the district of Kintamani , Bangli Regency. Data were obtained from census survey methods through techniques of 23 respondents Gapoktan Budi Luhur farmer groups implementing Simantri 116 in Bangli regency. Secondary data were obtained from the written literature related to the research. Results were analyzed using analysis of gross margin income of Rp 64,955,152 Rupiahs citrus, gross margine of bananas Rp 276,978 rupiahs, gross margine of cabbage revenue of 1,099,573 rupiahs and Rp 9,015,489 rupiahs cattle every year. The land produces citrus production of 643 tonnes , 14. 705 bananas, cabbage 10 tons and 23 cows. So the total revenue earned by Simantri 116 of 75,347,192 rupiahs. The results showed that the respondents have an average of 1,06 hectares of land area. Land used for crop production with livestock includes an average 0.85 hectares of land for citrus productions, the average land cattle production  00,01 hectares, 12,03 for cabbage production remainder is used for banana production. The results of the analysis of data with a simple linear programming approach and gross margin analysis. The use of a simple linear programming analysis to select a combination of several activities that can maximize the gross income and to evaluate the effect of uncertainty on the farm gross profit in hectare of farm land. Gross margin analysis aims to determine the total income of the respondents. Based on the results of the analysis of risk factors obtained gross profit of 1,629.876.554 rupiahs,  to 1,788,452,493 rupiahs admission fee of 158 575 938 rupiahs production facilities for all commodities in production with a maximum of 10 % of risk costs in hectare. Farmers who might avoid the risk of selecting plants that will generate a small but gross profit low risk, otherwise the plants will produce large gross profit but high risk. In this case the farmer would probably avoid the risk of selecting plants that will generate a small but gross profit low risk, otherwise the plants will produce large gross profit but high risk will be avoided so that farmers can increase farm income through a crop with livestock integration systems.